2009
DOI: 10.1088/0004-637x/708/2/1728
|View full text |Cite
|
Sign up to set email alerts
|

The Debris Disk of Vega: A Steady-State Collisional Cascade, Naturally

Abstract: The archetypical debris disk around Vega has been observed intensively over the past 25 years. It has been argued that the resulting photometric data and images may be in contradiction with a standard, steady-state collisional scenario of the disk evolution. In particular, the emission in the mid-infrared (mid-IR) appears to be in excess of what is expected from a "Kuiper belt" at ∼100 AU, which is evident in the submillimeter images and inferred from the majority of photometric points. Here we re-address the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 73 publications
(167 reference statements)
2
102
0
Order By: Relevance
“…Such a radial profile that rises outward with a sharp outer edge contrasts with those derived for the archetypal disks Vega (Su et al 2005;Krivov et al 2006;Müller et al 2010;Sibthorpe et al 2010) and β Pictoris (Golimowski et al 2006;Thébault & Wu 2008;Krivov et al 2009;Vandenbussche et al 2010). In these disks, the derived geometrical optical thickness typically falls off with a moderate r −1.5 relationship beyond the peak value, i.e.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Such a radial profile that rises outward with a sharp outer edge contrasts with those derived for the archetypal disks Vega (Su et al 2005;Krivov et al 2006;Müller et al 2010;Sibthorpe et al 2010) and β Pictoris (Golimowski et al 2006;Thébault & Wu 2008;Krivov et al 2009;Vandenbussche et al 2010). In these disks, the derived geometrical optical thickness typically falls off with a moderate r −1.5 relationship beyond the peak value, i.e.…”
Section: Resultsmentioning
confidence: 66%
“…The mass depends on the assumed initial size distribution. For collisional equilibrium, κ = −3.0, we would have M(s < 100 km) = 100 Earth masses, a value that is in-between the ones inferred for, e.g., A110, page 12 of 15 Vega (Müller et al 2010) and q 1 Eridani (Augereau et al, in prep.). For κ = −4.0, there would be only M(s < 100 km) = 0.7 Earth masses.…”
Section: Disk Mass and Long-term Evolutionmentioning
confidence: 53%
See 1 more Smart Citation
“…7, having subtracted the 70 µm-attributable component, overplotted with the expected thermal emission from fiducial discs of equal-sized grains with different optical properties, placed at a distance of 130 AU from an F6 V star. A comparison clearly demonstrates that grains smaller than a few tens of micrometres -those that are expected from collisional models (Krivov et al 2006;Thébault & Augereau 2007;Müller et al 2010;Löhne et al 2012) -yield emission that is too warm to be consistent with the observed fluxes. A rough agreement with the observations can only be achieved for larger grains ( > ∼ 1 mm), and only if they have low absorption at optical wavelengths (e.g.…”
Section: Circumstellar Emissionmentioning
confidence: 80%
“…The resulting brightness profiles were convolved with the instrumental PSF (see Sect. 2 in Müller et al 2010, for the algorithm used) and compared them with observed profiles.…”
Section: Surface Brightness Profilesmentioning
confidence: 99%